Etika Profesi Bimbingan dan Konseling: Asas Kerahasiaan Dalam Konseling Kelompok - Aristri, Ana (Universitas PGRI Semarang, 2024)
The purpose of this research is to discuss the role of ethics in the guidance and counseling profession, especially the principle of confidentiality in the group counseling process. This research method uses a literature review which examines several scientific articles resulting from previous research. The results of this research indicate that counselors have an ethical obligation to explain the importance of confidentiality during group counseling. The importance of implementing the principle of confidentiality in the implementation of counseling guidance because the success of counseling guidance depends on implementing the principle of confidentiality. This concept demands openness between the counselor and counselor as well as confidentiality of the client's problems.